Faktor-Faktor Yang Mempengaruhi Pendapatan Masyarakat Nelayan di Air Bangis - Alexander, Defri; Marwan, Marwan (Universitas Negeri Padang, 2024)
Direction of the aim of this study is to investigate the factors that have an effect on the income of fishing communities in Air Bangis, including working capital, fish prices, time spent at sea, and prior experience working at sea. A cross-sectional cross-sectional quantitative analytic field survey is this kind of research. The traditional assumptions of the data's normality, heteroscedasticity, and multicollinearity were tested prior to the use of multiple linear regression statistical tests in the analysis of the data. Working capital, fish prices, length of time at sea, and work experience at sea all had a 46,8.7% impact on fishermen's income, according to the R Square value of the results. This discussion provides a conclusion working capital variable has a significant impact on the income of fishing communities, that the fish price variable has a positive impact on fishermen's income that isn't too significant, and that the length of time spent at sea and work experience have no significant impact on fishermen's income. It is suggested to fishermen that they increase their fishing capital and gain access to more useful information in order to increase their income.